Global Production Network of Secondhand Clothes From New Zealand to Papua New Guinea - Hernandez-Curry, Maria (Auckland University of Technology, 2019)
It is not general public knowledge that each year, thousands of tonnes of secondhand clothing donated by New Zealand households is exported to Papua New Guinea. After donation by households, secondhand clothing is collected, sorted and retailed by charity organisations and one largescale for-profit firm in New Zealand. Garments are then exported to Papua New Guinea where they are retailed by a single for-profit firm. Some garments are purchased by street sellers from this retailer who then resell items to earn a living. This thesis has literally followed secondhand clothing from donators in New Zealand to consumers in Papua New Guinea using a Global Production Network framework. I have applied case study methodology, and woven principles of talanoa methodology into research design. Households and charities in Auckland, as well as SHC retailers and consumers in Port Moresby have been interviewed, observations made, and available trade data and online media content analysed. The purpose of this research is to find out about the pathways and quantities of traded secondhand clothing, understand the experiences of trade actors and the value they are able to extract from this commodity. Outcomes and mechanisms of this trade are described, and recommendations made for improving its sustainability.
Keywords: Global production network; Secondhand clothing; Pacific; Supply chain; Secondhand